Hester Prynne's Strategy of coping With The Exile Punishment In Nathaniel Hawthorne's The Scarlet Letter: An Individual psychological Perspective - NURWAHIDA, NIKEN (2012)
This research paper elaborates Hester Prynne strategy of coping with the exile punishment that is reflected in Nathaniel Hawthorne's The Scarlet Letter, which is analyzed through individual Psychological perspective. The objectives of the research are to analyze the novel based on its structural elements and based on the individual psychological theory, by identifying the relation between the theory and the main character. This research paper belongs to a qualitative research. The sources of the data come from both primary data source, which is The Scarlet Letter novel and secondary data sources are information about the author's biography, websites about the novel, and theory of individual psychological. The method to analyze the data is descriptive analysis. Having analyzed the novel, the researcher comes to the conclusion as follows: Firstly, based on the structural analysis, the researcher finds out the novel delivers a message that people need to find a way out their problem. Secondly, based on the individual psychological analysis it is clear that in this novel Nathaniel Hawthorne portrays consecutively Hester Prynne strategy of coping with the exile punishment in many ways.